A Targeted Swallow Screen for the Detection of Postoperative Dysphagia in Liver Transplant Patients. (March 2019) - Mukdad, Laith; Toppen, William; Nguyen, Son; Kim, Kwang; Mendelsohn, Abie H.; Zarrinpar, Ali; Benharash, Peyman
Introduction: Postoperative dysphagia leads to aspiration pneumonia, prolonged hospital stay, and is associated with increased mortality. We have demonstrated the validity of a bedside targeted swallow evaluation following cardiac surgery. Since dysphagia following liver transplantation is not well examined, we evaluated the efficacy of this swallow screen method in postoperative liver transplant patients. Methods: This was a prospective trial involving adult patients who underwent liver transplant surgery at our institution over a 5-month period. Within 24 hours of extubation and prior to the initiation of oral intake, all patients were evaluated using the targeted swallow screen, which is a direct assessment of mental status and laryngeal sensation/elevation upon swallowing of progressively larger amounts of water. A fiberoptic endoscopic evaluation of swallowing was requested for failed screenings. Results: During the study, 50 patients were screened. Twenty (40%) failed the targeted swallow screen, while 18 (90%)/20 failed the subsequent fiberoptic endoscopic examination (overall dysphagia incidence = 40%). Patients with dysphagia were older and had significantly longer intensive care unit and hospital stays. The screening test had a 90% sensitivity and a specificity of 83% for detecting dysphagia. Conclusion: The true incidence of dysphagia following liver transplantation appears to be significantly higher than previously recognized. A simple bedside swallow screen can efficiently screen these patients for dysphagia. Our findings require further validation and may support programs for reduction and early detection of dysphagia.